Documenting the impact of stroke in a middle-income country: a Malaysian case study. Issue 1 (2nd January 2020) - Mairami, Fatima Fanna; Warren, Narelle; Allotey, Pascale A.; Mak, Jun Shin; Reidpath, Daniel D.
Abstract: Purpose: Stroke is an abrupt event that often leaves survivors with long term disabilities, causing role changes, and financial strains on households. The profound impact of stroke on survivors may lead to a decline in quality of life due to the physical, psychological, and social difficulties they experience. Taking Malaysia as an example, this study aimed to explore the impact of stroke on survivors and how health services influence their recovery in low and middle-income countries (LMIC). Method: An ethnographic approach with data obtained primarily through in-depth interviews was used. Twenty-seven participants identified as having suffered a stroke were drawn from a health and demographic surveillance system in Malaysia. Results: The physical and social disruption of the lives of stroke survivors was intensified by the resultant financial constraints placed upon individuals, families and households, compounded by inadequate support from the health, and welfare systems. Despite the disruption to their lives, most participants were, at least in part, able to reestablish their lives through various factors that include a strong family support and active coping strategies. Conclusion: In LMIC, recovery can be shaped by the family unit and through active coping strategies especially those in relation to spirituality. Implications for rehabilitation: The impact of stroke on survivors and lack of specialized stroke care compromise the recovery process and quality of life for stroke survivors in low and middle-income countries. Support from the family and reinforcement of religious coping were judged to successfully aid recovery. Physical and emotional impairments as well as psychosocial wellbeing of survivors in the context of environmental factors need to be addressed.